Historical Review of Terrorism and Out-of-School Children Indoctrination and Radicalization: A Preliminary Investigation into the Child Abuse in the Boko Haram Suicide Bombing in Yobe Sate - Tahir, Lawan Jafaru; Alkali, Aisha (NIU Journal of Humanities, 2024)
This research paper intends to examine how the activities of terrorist cell especially those in West African sub-region initiates under age into their operation. The work looked at the nature of terrorism in Nigeria as to how their network spread to various parts of the country. It is believed most of the origin of the terrorism was influence by foreign ideology with specific target of a common belief. The paper also focused on the formation of the terrorists’ cell in Nigeria and how they succeeded by indoctrinating children into the main stream of terrorism for various missions. The research discusses the way and processes those terrorists followed or applied to achieve their objectives. It should be noted that throughout the period of the crisis, particularly in north-eastern Nigeria, there are several cases of attacks by the teenagers in various places with devastating effects on the society. It has been estimated that more 43% of the attacks in Yobe state which is the scope of the research and its surrounding has been attributed to suicide bombing attacks by either young girls or boys who were trained by the insurgents to attack their targets, with emphasis on the child abuse and radicalization, as well as how it affects the growth and development of youth in the society. Other aspect of consideration in the research include factors responsible for the successful enrolment and initiation of the underage into the organization. These factors include: poverty level of the society, materialism, ideological warfare, Islamism or secular radicalism, drugs addiction etc. Recent world report reveals that more than 20,000 people were killed and over two million displaced by the insurgency. Although the crisis has bedeviled almost 60% of the country, northeastern Nigeria was one of the most affected region of this terrible terrorist’s act. The overall effects of this indoctrination and radicalization of the youth by these groups have been a tremendous increased rate of crime within the region, hunger and starvation as well as general psychological trauma and fear of the unknown which was brought by the consequences of the general insecurity. The research also come up with the level of psychological damage done by the terrorists and examine whether the recent de-radicalization centers established by the Nigerian government shall serve its purpose or there is need for more measure to revert the victims back to the normal and official thinking of the decent society. Keywords: Children, Boko Haram, Indoctrination, Radicalization, Terrorism